2021
DOI: 10.1158/1538-7445.sabcs20-pd4-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD4-01: Preservation of axillary lymph nodes compared to complete dissection in T1-T2 breast cancer patients presenting 1-2 metastatic sentinel lymph nodes : A multicenter randomized clinical trial. Sinodar One.

Abstract: Introduction: Sentinel lymph node (SLN) staging is currently used to avoid complete axillary lymph node dissection (ALND) in breast cancer (BC) patients. The SLN is the only site of axillary metastasis (MTS) in ≤60% of cases. Recently, a randomized controlled trial (Z0011) comparing SLN biopsy (SLNB) alone with SLNB followed by ALND in patients with 1-2 SLNs+ demonstrated no significant statistical difference in relapse and overall survival rates among the two different groups. However, this study had some lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…Recently, SINODAR-ONE, a trial with a similar design as Z0011, reached similar conclusions [39]. In contrast to Z0011, only patients with macrometastases were enrolled and mastectomy was not an exclusion criterion.…”
Section: Scenario 2 Treatment Of the Axilla In Cn0/pn1(sn)mentioning
confidence: 82%
See 1 more Smart Citation
“…Recently, SINODAR-ONE, a trial with a similar design as Z0011, reached similar conclusions [39]. In contrast to Z0011, only patients with macrometastases were enrolled and mastectomy was not an exclusion criterion.…”
Section: Scenario 2 Treatment Of the Axilla In Cn0/pn1(sn)mentioning
confidence: 82%
“…ACOSOG Z0011 [37] AMAROS [38] SINODAR-ONE [39] OTOASOR [40] Patient number Abbreviations: DMFSdistant metastasis-free survival.…”
Section: Tablementioning
confidence: 99%
“…Indeed, the Z11 study showed excellent locoregional control with the omission of additional axillary surgery in patients with positive SLN. However, as in other studies that also evaluated the omission of axillary dissection at upfront surgery, patients submitted to NACT were not included in those analyses (45)(46)(47)(48)(49). Furthermore, residual disease following NACT means resistance to systemic treatment, hence the possibility of a high residual burden of disease.…”
Section: Positive Sln Following Nactmentioning
confidence: 99%
“…It should be performed in all patients with clinically and sonographically inconspicuous ALN status (cN0). The indication for ALND is increasingly limited to patients with high axillary tumour burden after several randomized trials failed to show an advantage for ALND in low, clinically occult tumour burden [45][46][47]. However, for these patients, there appears to be a benefit from radiotherapy of the axilla.…”
Section: Surgical Management Of the Axilla: In The Adjuvant Settingmentioning
confidence: 99%